Decision-making in cross-border cooperation in times of the COVID-19 pandemic - Schneider, Bettina (Jihočeská univerzita, 2021)
COVID-19 has caused unprecedented challenges to the decision-making process of cross-border cooperations. In consequence many cross-border cooperations are not able to travel abroad, leading to a fundamental shift from on-site to virtual collaboration. Existing research literature about decision-making and media use does not provide a thorough ex-planation of how the decision-making process changed and how the media is used. This study explores the change that the spread of the SARS-CoV-2 virus has presented and the technological means project managers use to implement their decisions. For this study, eight project managers were invited to participate in an expert interview and to talk about their experiences of making a decision while working from home. This thesis con-tributes to the Media Synchronicity Theory and Lunenburg's (2010) sequential model by providing an understanding of the procedure of the decision-making process and its media use during the COVID-19 pandemic. The change of the decision-making process resulted in more effort during the now more asynchronous preparation of this process. Moreover, it was found that more documents have been created to visually support this process at any step and the importance of the preparation team has increased. Finally, it was found that due to the change of situation, the decision-making has changed as well and more media is used to support the communication. However, concerning the decision-making itself, it could be observed that although there is a wide range of media to support the decision-making (e.g., voting tools, decision-making trees, decision matrix), hardly any are used.
Decision-making in cross-border cooperation in times of the COVID-19 pandemic
Keywords: cross-border cooperation; COVID-19; decision-making; decision-making process; Media Synchronicity Theory; cross-border cooperation; COVID-19; decision-making; decision-making process; Media Synchronicity Theory